PERAN PENGURUS TBM RUMAH PINTAR PUNGGUR CERDAS DALAM TRANSFORMASI BUDAYA LITERASI PADA MASYARAKAT DESA PUNGGUR KECIL - Margaretha, Hessy; Bahari, Yohanes; Utami, Patrisia Rahayu; Ramadhan, Iwan; Zatalini, Adhalia (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2026)
Literacy remains a significant challenge in Indonesia, particularly in rural areas, as reflected in low reading interest and literacy achievement. West Kalimantan Province, including Punggur Kecil Village in Kubu Raya Regency, is among the regions with relatively low literacy levels, highlighting the need for community-based literacy initiatives. This study aims to examine the role of the management of the Smart House Punggur Cerdas Community Reading Garden (Taman Bacaan Masyarakat/TBM) in fostering a literacy culture within the community. A descriptive qualitative approach was employed, with data collected through participatory observation, semi-structured interviews, and documentation involving TBM managers, community members, and village stakeholders. Data analysis followed qualitative descriptive procedures, including data reduction, data display, and conclusion drawing. The findings indicate that TBM managers act as agents of social change by serving as catalysts, mediators, information providers, and learning facilitators. Through structured, inclusive, and sustainable literacy programs, the TBM has contributed to gradual improvements in reading habits, learning attitudes, and the community’s ability to access, understand, and critically engage with information. Literacy transformation occurs across multiple levels, from performative to epistemic literacy, and is supported by community participation, cross-sector collaboration, and adequate facilities. However, challenges such as limited human resources and low reading interest among certain groups remain. Strengthening managerial capacity and ensuring sustained multi-stakeholder support are essential for maintaining literacy culture transformation in rural communities.